The Third Person Institute and Brief Review of the Gaps in the Administrative and Civil Procedural Law of Georgia Regarding This Institute - Ketevan Tsintsadze (European Scientific Journal, ESJ, 2017)
The present article deals with the important institute of the administrative and civil proceedings, such as the third person institute. This article provides a brief overview of the importance of the third person institute and the legislative gaps in the civil / administrative procedural law regarding this institute. In conclusion, the article presents possible solutions of relevant gaps and problems